Portal Venous Tumor Thrombosis and Visceral Organ Metastasis without Skeletal Involvement in mCRPC: Adverse Prognostic Indicators on Dual Tracer PET/CT and Clinical Outcome after 177Lu-PSMA-617 PRLT and Cabazitaxel Therapy - Edamadaka, Yeshwanth; Parghane, Rahul V.; Basu, Sandip (World Journal of Nuclear Medicine, 2024)
Prostate cancer involving visceral organs are occurrences in the later disease course, usually following regional nodal and skeletal involvement, and are refractory to conventional treatment. A 61-year-old male patient presented with locally advanced disease at presentation, which progressed on androgen deprivation therapy and systemic therapy with involvement of the visceral organs (lungs and liver). Portal venous tumor thrombosis involving the right and main branch was also observed on contrast-enhanced computed tomography (CECT) and magnetic resonance imaging (MRI), which showed intense uptake on 68Ga-labeled prostate-specific membrane antigen positron emission tomography/computed tomography (68Ga-PSMA-11 PET/CT) and 18F-fluorodeoxyglucose PET/CT (18F-FDG-PET/CT). Post-177Lu-PSMA-617 radioligand therapy (PRLT) showed mixed response on tumor marker and imaging analysis with survival of 6 months after 177Lu-PSMA radioligand therapy. The high Gleason score, visceral organ metastasis, and increased metabolic activity on FDG were the adverse prognostic factors in the described patient.
Keywords: prostate cancer; metastatic castration-resistant prostate cancer; liver metastasis; portal venous tumor thrombosis; 68Ga-PSMA-11 PET/CT; 18F-FDG-PET/CT; 177Lu-PSMA-617 radioligand therapy